The Effects of Fasting and Feeding on Preproinsulin Messenger RNA in Rats - Giddings, Stephen J. (1981)
The purpose of these experiments was to determine whether alterations in preproinsulin messenger (m)RNA activity could account for changes in insulin biosynthesis during fasting and refeeding. Rats were fasted 4 d and then fed for 6, 8, 24, or 48 h. With fasting, body weight decreased 25%, plasma glucose decreased from 6.1 to 2.2 mM, and pancreatic insulin content fell to 40% that of fed animals. Islet RNA decreased to 50% and protein to 55% that of control animals, while islet DNA content remained unchanged. After 6 h of refeeding, islet RNA content increased and was not significantly different from controls. Total islet and preproinsulin mRNA activity was estimated with an mRNA-dependent wheat germ cell-free protein synthesizing system. Preproinsulin and total protein synthesis was linearly dependent upon added RNA at concentrations up to 3 μg. Preproinsulin was identified by its mobility on SDS polyacrylamide gel electrophoresis and by hybrid arrested translation of preproinsulin mRNA. After an 18-h fast, islet mRNA activity decreased 33%; after 4 d mRNA activity decreased to 66% below that of control fed animals. Preproinsulin mRNA activity was decreased, but to a lesser extent, accounting for 20% of total islet protein in fed animals and 46% in the 4-d fasted animals. Total mRNA activity returned to control values after 8 h of refeeding and increased to 150% of controls at 24 and 48 h. Preproinsulin mRNA activity increased more rapidly on refeeding. By 8 h it was 160% of controls. To determine whether changes in preproinsulin mRNA activity were associated with changes in the amount of preproinsulin mRNA, nucleic acid hybridization analysis was performed. Pancreatic RNA from fed and fasted animals was electrophoresed on agarose gels, transferred to diazophenylthio paper, and hybridized to (32)P-labeled preproinsulin complementary (c)-DNA. This analysis demonstrated that changes in mRNA activity were associated with changes in the amount of hybridizable mRNA present. These studies are the first to demonstrate alterations of preproinsulin mRNA under any conditions, and the changes correlate with alterations in rates of insulin biosynthesis.